2024
DOI: 10.1001/jamainternmed.2023.6160
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bleeding Following Non–Vitamin K Antagonist Oral Anticoagulant Use in Patients With Acute Ischemic Stroke Treated With Alteplase

Tou-Yuan Tsai,
Yu-Chang Liu,
Wan-Ting Huang
et al.

Abstract: ImportanceCurrent guidelines advise against intravenous alteplase therapy for treatment of acute ischemic stroke in patients previously treated with non–vitamin K antagonist oral anticoagulants (NOACs).ObjectiveTo evaluate the risk of bleeding and mortality after alteplase treatment for acute ischemic stroke among patients treated with NOACs compared to those not treated with NOACs.Design, Setting, and ParticipantsThis nationwide, population-based cohort study was conducted in Taiwan using data from Taiwan’s N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…To the Editor We read with interest the nationwide population-based cohort study with meta-analysis by Tsai et al The study findings showed that patients who received non-vitamin K antagonist oral anticoagulants (NOACs) before a stroke, compared with those receiving warfarin and those without oral anticoagulant treatment (non-OAC), did not experience a higher risk of intracranial hemorrhage (ICH), major bleeding events, or mortality when treated with intravenous alteplase for acute ischemic stroke. In comparison with the active comparator (warfarin group), the odds ratios (ORs) were 0.88 (95% CI, 0.32-2.40) for ICH, 0.82 (95% CI, 0.34-1.97) for major bleeding, and 0.31 (95% CI, 0.08-1.18) for in-hospital mortality.…”
mentioning
confidence: 99%
“…To the Editor We read with interest the nationwide population-based cohort study with meta-analysis by Tsai et al The study findings showed that patients who received non-vitamin K antagonist oral anticoagulants (NOACs) before a stroke, compared with those receiving warfarin and those without oral anticoagulant treatment (non-OAC), did not experience a higher risk of intracranial hemorrhage (ICH), major bleeding events, or mortality when treated with intravenous alteplase for acute ischemic stroke. In comparison with the active comparator (warfarin group), the odds ratios (ORs) were 0.88 (95% CI, 0.32-2.40) for ICH, 0.82 (95% CI, 0.34-1.97) for major bleeding, and 0.31 (95% CI, 0.08-1.18) for in-hospital mortality.…”
mentioning
confidence: 99%
“…Regarding the results on intracranial hemorrhage (ICH) development, the primary outcome measure in our study was the development of any type of ICH, including symptomatic or asymptomatic ICH. We used codes 433 and 434 from the International Classification of Diseases, Ninth Revision, Clinical Modification and codes I63 and I64 from the International Statistical Classification of Diseases, Tenth Revision, Clinical Modification during the index hospitalization per the Taiwan National Health Insurance Research Database records.…”
mentioning
confidence: 99%
“…To the Editor In their population-based cohort study using Taiwan’s National Health Insurance Research Database, Tsai et al report no excess risk of intracranial hemorrhage (ICH) associated with treatment compared with no treatment with non-vitamin K antagonist oral anticoagulants (NOACs) in patients with acute ischemic stroke receiving intravenous alteplase. We applaud the authors’ efforts to build on the evidence on the safety of thrombolysis in patients receiving NOACs; however, we wonder about potential issues of exposure and outcome misclassification producing results that are biased toward the null hypothesis.…”
mentioning
confidence: 99%
“…The authors used prescriptions for anticoagulants from insurance claims data to identify exposed and unexposed groups of patients who were treated compared with untreated with NOACs, respectively . Although these data are relatively complete and generally superior to self-reported use of medication, they do not capture medication nonadherence.…”
mentioning
confidence: 99%
See 1 more Smart Citation